BUILDING CUSTOMER LOYALTY THROUGH STRATEGY EXPERIENTIAL MARKETING, SERVICE QUALITY, AND CUSTOMER SATISFACTION - Wahyono, Wahyono; Nurjanah, Ulfa (Management Analysis Journal, 2020)
The study aims to determine the influence of Experiential Marketing, quality of service, and customer satisfaction towards customer loyalty by developing a research model and 6 hypotheses filed in this study. The number of samples was 160 respondents, namely the customer of PT POS Indonesia (Persero) Semarang with incidental sampling through questionnaires. Data analysis using Structural Equation Modeling (SEM) of Software AMOS 21.0 based on data analysis results, it can be concluded that the model received good/fit and subsequent research results showed there were 3 hypotheses received and 3 hypotheses were rejected.